2020
DOI: 10.1242/dev.183509
|View full text |Cite
|
Sign up to set email alerts
|

Human antigen R-regulated mRNA metabolism promotes the cell motility of migrating mouse neurons

Abstract: Neocortex development during embryonic stages requires the precise control of mRNA metabolism. Human antigen R (HuR) is a well-studied mRNA-binding protein that regulates mRNA metabolism, and it is highly expressed in the neocortex during developmental stages. Deletion of HuR does not impair neural progenitor cell proliferation or differentiation, but it disturbs the laminar structure of the neocortex. We report that HuR is expressed in postmitotic projection neurons during mouse brain development. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Western blot procedures were performed as previously described [ 22 , 23 ]. Briefly, mouse cortices were lysed in RIPA buffer contained SDS, boiled at 100 ℃ for 5 min, and run on 6–12% Bis–Tris gel.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot procedures were performed as previously described [ 22 , 23 ]. Briefly, mouse cortices were lysed in RIPA buffer contained SDS, boiled at 100 ℃ for 5 min, and run on 6–12% Bis–Tris gel.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism partially takes place through the stabilization of F-actin modulator, Profilin1 mRNA, upon Elavl1 binding to its 3 UTRs. OE of Profilin1 in Elavl1 cKOs neurons thus rescued the migratory phenotype (Zhao et al, 2020). The loss of another RBP, RNA-binding motif 4 (Rbm4), results in elevated levels of Disabled-1 (Dab-1) isoform lacking tyrosineencoding exons 7/8, which causes a severe migratory deficit and aberrant positioning of the later-born neurons in the mouse embryos.…”
Section: Establishment Of the Unique Layered Structure Of The Neocortexmentioning
confidence: 99%
“…Again, RBPs appear to be major players in regulating the later steps of neuronal migration. Zhao et al (2020) showed that the deletion of RBP Elavl1 in post-mitotic neurons affects F-actin dynamics, which translates into the delayed cell motility of later-born neurons without any effect on the multipolar–bipolar transition or neuronal polarization. As a result, Elavl1 cKO later-born neurons preferentially localized in the deeper, instead of the upper, cortical layers in the mouse embryonic neocortices.…”
Section: Establishment Of the Unique Layered Structure Of The Neocortexmentioning
confidence: 99%
“…In the development of the neocortex, the deletion of ELAVL1 reduces the phosphorylation of eIF2a and eEF2 and the formation of polysomes, ultimately leading to the mis-localization of mRNAs. The lack of ELAVL1 reduces the stability of PFN1 mRNA and affects actin polymerization, resulting in the mis-localization of neurons in the neocortex ( Kraushar et al, 2014 ; Zhao et al, 2020a ). It also participates in cellular metabolism and protection from oxidation-induced neurodegeneration ( Skliris et al, 2015 ).…”
Section: Elavl Proteins In Pathological and Physiological Processesmentioning
confidence: 99%
“…Biologically, ELAVL proteins were originally discovered as indispensable regulators of nervous system development and physiological function ( Rogulja-Ortmann et al, 2014 ; Wang et al, 2019a ; Zhao et al, 2020a ). Interestingly, subsequent studies have shown that they not only exist in the nervous system, but also have regulatory effects in other tissues, including hepatocytes ( Wang et al, 2021 ), fat cells ( Siang et al, 2020 ), vascular smooth muscle cells ( Liu et al, 2020a ), and intestinal epithelial cells ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%